1998
DOI: 10.1080/00207149808409992
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic analgesia: 1. somatosensory event-related potential changes to noxious stimuli and 2. transfer learning to reduce chronic low back pain

Abstract: Fifteen adults with chronic low back pain (M = 4 years), age 18 to 43 years (M = 29 years), participated. All but one were moderately to highly hypnotizable (M = 7.87; modified 11-point Stanford Hypnotic Susceptibility Scale, Form C [Weitzenhoffer & Hilgard, 1962]), and significantly reduced pain perception following hypnotic analgesia instructions during cold-pressor pain training. In Part 1, somatosensory event-related potential correlates of noxious electrical stimulation were evaluated during attend and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 76 publications
5
32
0
Order By: Relevance
“…More recently, Crawford (1994) and Crawford, Knebel, Kaplan and Vendemia (1998) targeted attentional mechanisms, hypothesizing that these involve the frontal and limbic areas of the brain, in line with Gruzelier and Warren (1993) who suggested that inhibitory functions of the frontal lobe and limbic systems may contribute to peripheral nervous system effects of hypnosis in general, not solely pain modulation effects.…”
Section: Attention Hypnosis and Hypnotic Analgesiamentioning
confidence: 88%
See 2 more Smart Citations
“…More recently, Crawford (1994) and Crawford, Knebel, Kaplan and Vendemia (1998) targeted attentional mechanisms, hypothesizing that these involve the frontal and limbic areas of the brain, in line with Gruzelier and Warren (1993) who suggested that inhibitory functions of the frontal lobe and limbic systems may contribute to peripheral nervous system effects of hypnosis in general, not solely pain modulation effects.…”
Section: Attention Hypnosis and Hypnotic Analgesiamentioning
confidence: 88%
“…Extensive experimental work that substantiates involvement of the frontal and limbic areas of the brain has been done by Crawford and colleagues (Crawford et al, 1993a;Crawford, 1994;Crawford et al,1998). These authors have related inhibitory patterns of brain activity, including theta rhythm in the EEG, to the disattention resulting from suggestions for hypnotic analgesia (not to be confused with distraction).…”
Section: Cortical Mechanisms: 2 Electroencephalographic Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Hypnosis has also been linked to theoretical accounts of pain and its origins. Crawford, Knebel, Kaplan and Vendemia (1998), for example, have identified a link between high hypnotic suggestibility and chronic pain. Wickramasekera, Pope and Kolm (1996) and Wickramasekera (1998) cite high or low hypnotic susceptibility in conjunction with high social desirability scores as a risk factor for chronic pain within his high-risk model of threat perception.…”
Section: Introductionmentioning
confidence: 96%
“…The use of hypnosis in the treatment of pain as well as for other medical and psychological conditions is an old practice that mainly consists on techniques designed to develop a state of mental ease and absorption that heighten responsiveness to suggestions oriented to produce changes in subjective experience [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%